Efficient Somatic Embryogenesis and Plantlet Regeneration Induced from Mature Embryo Culture under Heavy Metals Stress Conditions in a Millet Crop Sorghum [Sorghum bicolor (L.) Moench] - Roselin Roobavathi, M.; Vikrant (Journal of Stress Physiology & Biochemistry, 2025)
The present study aims to establish the somatic embryogenesis and plantlet regeneration in Sorghum bicolor (cv. PAC501) under heavy metals (lead and cadmium) stress conditions. Mature embryos were inoculated in MS-medium containing (10mg/L, 25mg/L, 50mg/L, 75mg/L, and 100mg/L) of PbSO4 and CdCl2 (10mg/L, 25mg/L, 50mg/L, 75mg/L, 100mg/L, 150mg/L, and 200mg/L) each with IAA (1.0mg/L), BAP (0.5mg/L), zeatin (0.1mg/L), and proline (0.7mg/L). Significantly, high frequency (87.2±0.21%) of somatic embryogenesis was initially obtained with IAA (1.0mg/L), BAP (0.5mg/L), zeatin (0.1mg/L), and proline (0.7mg/L) while in comparison, 2,4-D (2.5mg/L) along with same concentrations of BAP, zeatin, and proline was proved as relatively less efficient (67.4±0.64%) for somatic embryogenesis. Furthermore, results reveal that sub-culture of embryogenic callus on cytokinins; BAP, Kn, and Zn (0.1mg/L, 0.5mg/L, and 1.0mg/L) of each added regeneration medium, kinetin (0.5mg/L) was recorded as the most effective cytokinin (77.8±0.93%) for plantlets regeneration. Moreover, during heavy metals treatments, the least frequency (2.9±3.32%) of lead tolerant somatic embryos was obtained with PbSO4 (75mg/L) in presence of the same concentrations of IAA, BAP, zeatin, and proline. Significantly, the very low frequency (3.7±0.67%) of lead tolerant plantlets regeneration was recorded with PbSO4 (75mg/L) and Kn (0.5mg/L). In contrast, during CdCl2 stress treatment, the cadmium tolerant somatic embryos (3.1±3.24%) were obtained with CdCl2 (150mg/L) and IAA, BAP, zeatin, and proline. Further, cadmium tolerant plantlets (4.23±2.33%) were also achieved on medium containing kinetin (0.5mg/L) with CdCl2 (100mg/L) indicating that lead proves to be more toxic for somatic embryogenesis and plantlets regeneration than cadmium. Later, the regenerated tolerant plantlets were transferred to pots and gradually acclimatized in greenhouse.